Developing Thinning and Pruning Guidelines for Acacia Mangium Plantations in Peninsular Malaysia Using Tree Growth Characteristics - Paudyel, Bimal keshari (1990)
Peninsular Malaysia is expected to face a timber deficit before the end. of the century. the compensatory Forest Plantation Project now undertaken as a remedial measure for this impending crisis needs research in plantation management perticularly on silvicultural practices such as thinning and pruning. thinning needs primary attention in plantation forestry if the management objective is sawlog production. The present study focusses mainly on the determination of reasonable age for first thinning in Acacia mangium plantation in Peninsular Malaysia. In addition to the preliminary thinning study, pruning trials and evaluation of growth pattern of Acacia mangium in different aged stands and on different sites were also conducted. three sites, that is, Kemasul in Pahang, Setul in Negeri Sembilan and Rantau Panjang in Selangor were chosen for the study.